WOMEN`S MOTIVATION TO ENGAGE WITH THE NORDIC WALKING - Upeniece, Irēna; Vīnberga, Indra; Arnis, Voldemārs; Erts, Renārs (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
Physical activity beneficial effects on human health in various aspects are proved by many research. In woman's health status maitenance and strengthening the important role has physical activitities. People engage with physical activities encourages a number of factors. Nordic walking as a physical activity has many benefits that would motivate women of different ages to engage with the Nordic walking. The research group was formed of 100 women between the ages of 25 -82 years. According to the World Health Organisation female age division (20), was created the following age groups (women from 25 to 44 years, 32 participants, women from 45 to 59 years, 35 participants, women from 60 to 82 years, 33 participants). Respondents attitude measurement was used Likert scale (Likert Scale, 2007) with 15 allegations. The obtained results show that the motivating factors as location outdoors in the fresh air, the joy of physical activity and health improvement is important for women of any age to engage with the Nordic walking. There are more differences between the participants of the age groups view about the factors as a stress reduction, pleasant instructor presence, society attitude, socialization process. For the younger women more important motivating factor is a stress reduction, middle-aged women, the weight adjustment, and older women, the opportunity to socialize or meet other people, compared with the other age groups. Literature data and the results of research allow to recommend Nordic walking for women regardless of age.